2009
DOI: 10.1017/s1751731108003546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size of alfalfa hay and reconstitution with water on intake, digestion and milk production in Holstein dairy cows

Abstract: Twenty-four lactating Holstein dairy cows (12 first lactation and 12 multiparous; day in milk 5 11 6 5 days) were allotted to a randomised complete block design in a 2 3 3 factorial with four replicates per treatment to evaluate the effects of two methods of alfalfa feeding (dry and reconstituted to achieve a theoretical dry matter (DM) content of 350 g/kg) and three geometric mean (GM) particle sizes of alfalfa (9.13, 4.51 and 1.20 mm) on performance of dairy cows for a period of 28 days. Diets were offered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Therefore, compared with barley, BP created more favorable conditions for microbial utilization of other carbohydrates in the rumen, at least in part due to the neutral pH. Decreasing daily mean ruminal pH, which was associated with an increase in ruminal outflow rate of digesta, resulted in a decrease in ruminal NDF digestibility and total tract digestibility [2,8,9,33]. Zebeli et al [9] showed a decrease in total tract NDF digestibility by increasing the outflow rate of particulate digesta, which was associated with a decrease in ruminal mat consistency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, compared with barley, BP created more favorable conditions for microbial utilization of other carbohydrates in the rumen, at least in part due to the neutral pH. Decreasing daily mean ruminal pH, which was associated with an increase in ruminal outflow rate of digesta, resulted in a decrease in ruminal NDF digestibility and total tract digestibility [2,8,9,33]. Zebeli et al [9] showed a decrease in total tract NDF digestibility by increasing the outflow rate of particulate digesta, which was associated with a decrease in ruminal mat consistency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a clear negative relationship between particle density and ruminal mean retention time. Particles with a specific gravity of lower than the critical size (1.18 mm) quickly pass out of the reticulorumen [8]. The specific gravity for BP was 1.152, whereas that of barley and corn grain were higher than 1.237 [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations